Are the "critical" inspiratory constraints actually decisive to limit exercise tolerance in COPD?. Issue 3 (17th August 2020) - Marillier, Mathieu; Bernard, Anne-Catherine; Gass, Ricardo; Berton, Danilo C.; Verges, Samuel; O'Donnell, Denis E.; Neder, J. Alberto
Exercise intolerance is characteristically multi-factorial in patients with chronic obstructive pulmonary disease (COPD) [1]. At least in symptomatic patients with moderate-to-severe airflow limitation, higher operating lung volumes assume a relevant role in decreasing patients' tolerance to sustain "prolonged" exercise. As a consequence of the dynamic increase in the end-expiratory lung volume, tidal volume (VT) occurs close to total lung capacity (TLC), thereby reducing the room for further lung–chest wall expansion. The combination of low dynamic lung compliance and a severely reduced inspiratory reserve volume causes a mismatch between a growing respiratory neural drive and the resulting lung–chest wall displacement [2]. It has been postulated that such critical inspiratory constraints (CIC) lead to a plateau in VT, and a concomitant increase in dyspnoea as a function of ventilation ( V ′E ) [3]. Accordingly, patients change their perception of the uncomfortable respiratory sensations from "laboured breathing" to "insufficient inspiration", prompting early exercise termination [4]. The concept of critical inspiratory constraints is key to the modern understanding of exercise pathophysiology in patients with moderate-to-severe COPD https://bit.ly/2A6bCxD